2018
DOI: 10.1029/2018gl078608
|View full text |Cite
|
Sign up to set email alerts
|

The Signature of Ozone Depletion in Recent Antarctic Precipitation Change: A Study With the Community Earth System Model

Abstract: Although precipitation is a primary control on Antarctic ice sheet (AIS) mass balance, long‐term historical AIS precipitation trends and their underlying external climate drivers remain inconclusive. In this study, we use a novel pair of climate model ensembles to identify a simulated spatial signature of ozone depletion‐forced AIS precipitation change. Distinct areas of little change or precipitation decrease, arising from interaction between ozone depletion‐forced atmospheric circulation changes and ice shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…SMB is predicted to increase at a rate of ~100 Gt/year per degree of (near‐surface AIS) warming (Ligtenberg et al, ) by the mechanism of enhanced water vapor concentration in a warmer atmosphere. Additionally, changes in atmospheric dynamics, in turn driven by global warming, stratospheric ozone recovery, and/or natural variability, have recently been suggested to influence Antarctic SMB trends (Lenaerts et al, ; Medley & Thomas, ). Finally, changes in cloud phase and structure over Antarctica, sea ice decline, and ocean surface warming have been suggested to control AIS SMB into the future (Lenaerts et al, ).…”
Section: Future Ice Sheet Smb: Projections Feedbacks Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…SMB is predicted to increase at a rate of ~100 Gt/year per degree of (near‐surface AIS) warming (Ligtenberg et al, ) by the mechanism of enhanced water vapor concentration in a warmer atmosphere. Additionally, changes in atmospheric dynamics, in turn driven by global warming, stratospheric ozone recovery, and/or natural variability, have recently been suggested to influence Antarctic SMB trends (Lenaerts et al, ; Medley & Thomas, ). Finally, changes in cloud phase and structure over Antarctica, sea ice decline, and ocean surface warming have been suggested to control AIS SMB into the future (Lenaerts et al, ).…”
Section: Future Ice Sheet Smb: Projections Feedbacks Uncertaintiesmentioning
confidence: 99%
“…In response to ENSO, eastern West Antarctica experiences anomalously low sea surface temperatures (SSTs) and an atmospheric moisture flux directed away from the ice sheet, while western West Antarctica (the region around the Ross ice shelf) experiences higher than normal SSTs and anomalously high southward moisture fluxes (Marshall et al, ; Marshall & Thompson, ). Additionally, recent work suggests that stratospheric ozone depletion, apart from impacting Southern Ocean sea ice and atmospheric dynamics, has led to a spatial redistribution of Antarctic snowfall, and an increase in total snowfall (Lenaerts et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the large internal variability makes detection of a statistically-significant signal in SMB difficult, modeling suggests that stratospheric ozone depletion acting alone would drive an increase in Antarctic SMB [148]. However, sea ice extent appears to be an important factor in Antarctic precipitation trends [149] and the response of sea ice to stratospheric ozone depletion in models has been found to be highly model dependent [150].…”
Section: Smbmentioning
confidence: 99%
“…Reanalyses and RCM simulations often serve as references for evaluating the performances of General Circulation Models (GCMs), among which those involved in the fifth Coupled Model Intercomparison Project (Lenaerts et al, 2016;Previdi & Polvani, 2016;Palerme et al, 2017). Reanalyses, RCMs, and GCMs are also powerful tools to carry out climatological studies to assess the response of the Antarctic precipitation to the atmospheric circulation patterns (Genthon et al, 2003;Marshall et al, 2017;Monaghan et al, 2008), to the ozone depletion (Lenaerts et al, 2018), or to climate change (Palerme et al, 2017). Regarding the model performances, it 10.1029/2019JD031028 has been shown that the simulated Antarctic precipitation field strongly depends on the horizontal resolution (Genthon et al, 2009) and on the sea surface boundary conditions (Kittel et al, 2018;Krinner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%